Concepts of database management - Pratt, Philip J.; Adamski, Joseph J. (Boston, Massachusetts Thomson Course Technology, 2005)
This book introduction to data-base competes. The two featured case problems, Premiere Products and Henry Books, bring to life real-world database issue such as database design, data integrity, concurrent updates, and data security. [It] include[s] expanded coverage of SQL, entity-relationship (E-R) diagrams, normalization, and data-base design.
Keywords: Công nghệ thông tin